2022
DOI: 10.3390/ma15175956
|View full text |Cite
|
Sign up to set email alerts
|

Ti64/20Ag Porous Composites Fabricated by Powder Metallurgy for Biomedical Applications

Abstract: We present a novel Ti64/20Ag highly porous composite fabricated by powder metallurgy for biomedical applications and provide an insight into its microstructure and mechanical proprieties. In this work, the Ti64/20Ag highly porous composites were successfully fabricated by the space holder technique and consolidated by liquid phase sintering, at lower temperatures than the ones used for Ti64 materials. The sintering densification was evaluated by dilatometry tests and the microstructural characterization and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, the addition of such metals leads to dense materials with high stiffness [15,19]. In order to reduce the stiffness, scaffold of Ti-10Cu [20] and Ti64-20Ag alloys [21] were fabricated by the space holder method. Young's modulus values lower than10 GPa were obtained with around 50% porosity, which is close to bone implant requirements.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of such metals leads to dense materials with high stiffness [15,19]. In order to reduce the stiffness, scaffold of Ti-10Cu [20] and Ti64-20Ag alloys [21] were fabricated by the space holder method. Young's modulus values lower than10 GPa were obtained with around 50% porosity, which is close to bone implant requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The space holder technique was first used because it offers the possibility to control the pore features in function of the type of the pore formers used, their shape and their quantity. This technique has been used to produce highly porous materials, and different works have been devoted to studying the mechanical properties [ 7 , 8 , 9 , 10 , 11 ]. It was demonstrated that the mechanical strength of the porous materials can be diminished up to that of the human bones by controlling the pore volume fraction [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of mechanical behavior is usually included, however, without any general and exact description of the relationship between mechanical behavior and structure and composition. We can mention some examples as regenerated cellulose + cross-linked poly (ethylene glycol) for potential biomedical applica-tions, packaging, and sewage purification with a higher rate of porosity reaching 97% [35], properties of glass-ceramic binder doped by nanocopper [36] alloy of titanium, aluminum, and vanadium with the addition of silver particles for biomedical applications up to 50% of porosity [37], even combination of ceramics and epoxy resin or polycaprolactone with approximately 70% of porosity [38].…”
Section: Introductionmentioning
confidence: 99%